Fenomena Fear of Missing Out (FOMO) terhadap Keputusan Pembelian Donut of Curiosity - Lim, Chelsea; Genoviene, Feliska; Riyanto, Budi; Abdillah, Fitri (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The food and beverage industry in Indonesia has experienced rapid growth, driven by increasing consumer demand and trends influenced by social media. This study examines the application of Fear of Missing Out (FOMO) marketing strategies at Donut of Curiosity, a pumpkin donut shop located in Ashta District 8, South Jakarta. The research adopts a quantitative approach by collecting data through likert scale questionnaires distributed to 100 respondents selected using purposive sampling. Data analysis was conducted using descriptive statistics and correlation tests. The findings reveal that FOMO marketing strategies have an effective impact on influencing purchasing decisions. FOMO indicators, such as fear, anxiety, and self-esteem, have a significant influence on consumer behavior. The alternative evaluation stage and post-purchase behavior emerged as the most prominent aspects of the purchasing decision process, where consumers are motivated to buy and recommend the product after gaining social and emotional benefits. The correlation test shows a positive relationship between FOMO and purchasing decisions, with a relatively strong correlation value. These findings provide practical implications for business practitioners to optimize FOMO marketing strategies while maintaining product quality and enhancing customer experiences to strengthen customer loyalty.